Bankruptcy of claimant and representation under section 20(1) of the Industrial Relations Act 1967: whether previous sanction of the Director General of insolvency required? - Ali Mohamed, Ashgar Ali; Sardar Baig, Farheen Baig; Kasi, Arun (CLJ Bulletin, 2018)
This extended power to award backwages and compensation has, in practice, quite commonly triggered an argument on the part of the employer, if the workman is an undischarged bankrupt, that sanction of the Director General of Insolvency is required in order for the workman to pursue the action under the s. 20 of the IRA 1967. In other words, whether it is competent for the reference to proceed under the s. 20 of the IRA 1967 in the absence of the sanction when the workman is an undischarged bankrupt? This is the question that this article intends to deliberate and put in right a perspective.